Chaotic characteristics of thermal convection at smaller verse larger Prandtl number through fractal and fractional differential operators from nanofluid. (2nd January 2023) - Abro, Kashif Ali; Souayeh, Basma; Malik, Kamran; Atangana, Abdon
ABSTRACT: Nanofluids with a smaller and larger Prandtl number reflect the dominations of thermal diffusivity and momentum diffusivity, respectively. This fact shows how much heat is carried away by how much fluid through transference from one point to another point. For the sake of the above fact, the thermal convection at a smaller versus larger Prandtl number through fractal and fractional differential operators is investigated from the nanofluid on the basis of certain nanoparticles and base fluid. The nanofluid as a base fluid is ethylene glycol and nanoparticles are titanium dioxide, copper, silver and aluminium oxide. For the first time in the literature, mathematical modeling is proposed via fractal and fractional differential operators of Caputo-Fabrizio and Atangana-Baleanu. The numerical schemes of chaotic models have been presented by invoking the Adams-Bashforth-Moulton method as a powerful technique for simulations. The thermophysical properties of the nanofluid have been traced out chaotically by comparative analysis of fractal and fractional differential operators of Caputo-Fabrizio and Atangana-Baleanu. Finally, two-dimensional chaotic attractors, three-dimensional chaotic attractors and each type of nanoparticle have been discussed for smaller, medium and larger values of Prandtl number by emphasizing the role of fractal and fractional differential operators.